ANALYSIS OF LEARNING LOSS: AN INSIGHT FROM BIOLOGY EDUCATION DEPARTMENT - Anak Agung Inten Paraniti; Ni Komang Dina Suciari (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2025)
The process of transitioning face-to-face learning to online learning requires rapid adjustments by teachers and students to the learning process, and if not, it can lead to learning loss. Only view studies have been done related to learning loss, therefore this study aims to analyze a) differences in learning before and after the pandemic, b) learning loss during the pandemic, c) the factors that caused learning loss during the pandemic, d) efforts that can be applied to tackle learning loss. This research was a qualitative descriptive study with a phenomenological approach located at Mahasaraswati University Denpasar with a sample of 65 participants include lecturers and students. Data collection techniques were carried out by observation, interviews, documentation, and triangulation. The result of this study is a complex description of learning loss analysis. The conclusion of the research shows that learning loss occurs in various aspects such as learning time, learning attitude, process ability, knowledge, and learning process.